Smart Gas Leak Detection And Emergency Response System Using Iot For Homes - Abdul Salam Shah; Amar Dinesh; Asadullah Shah; Mirza Farooq; Adil Maqsood; Muhammad Adnan Kaim Khani (Journal of ICT, Design, Engineering and Technological Science, 2024)
As we know, safety is a massive problem in this world today. We can use technology to combat the issue of safety. One of the safety issues is gas leakage, which caused the accident. In this project, we design and develop a system that is based on IoT and detects and monitors gas leakage in real time in homes and small businesses. The project uses NodeMCU as a microcontroller, gas sensors, and other devices like the Wi-Fi module, servo motor, and exhaust fans. This project shows how to integrate different hardware components and hardware with software. The traditional gas detectors found in the market can only alert the user through audio and visual alerts that are only viable if a person is present to combat the issue; what this project does is not only alerts using audio and video, it also alerts the user and the emergency department using a notification sent to an application in the mobile phone. The integration of the app not only increases user interface experience and responsive time but also allows the user to adjust the system's parameters through the app and gives real-time status to prevent accidents; the project also deploys prevention measures such as opening the window, turning on the exhaust, and shutting off the main gas valve to avoid chances of fireand damage.